Pengaruh Islamic Leadership Terhadap Kinerja Karyawan Melalui Kepuasan dan Motivasi Kerja Karyawan Sebagai Variabel Intervening Pada PT. Bank Syariah Indonesia Kantor Area Malang - Rizal, Rifki Zuhdi; Widarko, Agus; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This study aims to analyze and explain the effect of Islamic leadership on employee performance through job satisfaction and motivation as intervening variables at PT Benih Citra Asia Jember. 67 respondents were selected for the study's sample using a random sampling approach based on the Slovin formula. This study employed route analysis (also known as path analysis) as a quantitative data analysis tool. Partial hypothesis testing using data is employed. As per the study's findings, there is a noteworthy correlation between the variables of Islamic leadership and employee performance. Additionally, there is a noteworthy effect of Islamic leadership on job satisfaction and work motivation. Furthermore, there is a sigificant relationship between work motivation and employee performance and job satisfaction variables. While the indirect effect shows that the job satisfaction variable is able to mediate the Islamic leadership variable on employee performance, the work motivation variable is also able to mediate the Islamic leadership variable on employee performance.Â Keywords: Islamic Leadership, Job Satisfaction, Work Motivation, Employee Performance.